Vitruvii Basilicana et cetera - Ohr, Karlfriedrich (KIT Scientific Publishing, 2019)
Seven Essays on Vitruvius and his Instructions on the Building of Basilicas, on The Basilica and here architectural Derivation of the greek Stoa, on the Basilica Aemilia at the Forum Romanum, on Architectural Scale Plans in the Antiquity und on dubious Reconstructions of Basilicas.